"Contemporary Croatian Film and the New Social Economy" - Šesnić, Jelena (Array, 2011)
A reading of several contemporary Croatian films (O. Sviličić's "Sorry about the Kung-Fu" ; H. Hribar's "What Is a Man without a Moustache" ; T. Radić's "What Iva Recorded...") from the point of view of feminist and cultural perspectives and refracted especially through the notion of local spaces affected by global cultural processes. Focusing on the examples of decentred female characters in such locations, the analysis contends that a regional space becomes representative albeit ambivalent factor of globalization bringing in its wake also a model of revised gender roles. Such transformations are rendered visible in each of the films through specific generic, stylistic and thematic features addressed in the article. The transitional economy, especially in the way cultural commodities are shown to circulate in each of these films, may bring about new family structures, a revised model of gender relations and new intimate spheres, or they may simply indicate a new realignment in a global cultural economy.